Design of the intelligent control system traction drives - Кулагін, Дмитро Олександрович; Роменський, Ігор Сергійович (Eastern-European Journal of Enterprise Technologies, 2015)
This paper studies for the creation of intellectual control system for electric traction. The analysis was further developed methodology development of intelligent control systems for electric vehicles by developing a neural network systems using swarm intelligence for optimum traction rolling electrical complex that lets you set partial traction by means of electric transmission with minimum mean square error values. The paper presents the intellectual electric traction control system based on the following sequence: synthesis control system to provide the necessary connection between the parameters of the dynamics and traction characteristics necessary traction motors using Particle swarm optimization, which makes it impossible to establish a clear connection between the parameters of traction dynamics and the desired characteristics of traction motors; development of appropriate neural network technology to ensure the functioning of the developed system.